CoS2 / MoS2 self-supporting heterojunction catalyst as well as preparation method and application thereof

By synthesizing a spin-polarized CoS2/MoS2 heterojunction catalyst on a single crystal CoMoO4 precursor, the problem of insufficient activity and stability of existing SOR catalysts is solved, and efficient and stable sulfide ion oxidation reaction and energy-saving hydrogen production are achieved. Effect.

CN119332288AActive Publication Date: 2025-01-21CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411461924.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

In the prior art, the catalytic activity and stability of transition metal-based SOR catalysts are poor, making it difficult to meet the needs of industrial applications of large currents.

Method used

A spin-polarized CoS2/MoS2 heterojunction catalyst was successfully synthesized on a single crystal CoMoO4 precursor through hydrothermal method and thermal sulfidation method, and was applied in the sulfide ion oxidation reaction of electrocatalytic seawater electrolysis for hydrogen production.

Benefits of technology

The catalyst achieves high activity and stability, can operate stably for more than 70 hours under high current, and has excellent SOR catalytic activity and energy-saving hydrogen production effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332288A_ABST
    Figure CN119332288A_ABST
Patent Text Reader

Abstract

The invention discloses a spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst and a preparation method and application thereof.The preparation method comprises the steps that a single crystal CoMoO4 nanorod is synthesized on foamed nickel through a hydrothermal method, and a precursor CoMoO4 / NF is obtained; and cutting the precursor CoMoO4 / NF, placing the cut precursor CoMoO4 / NF in the downstream of a tubular furnace, and carrying out heat vulcanization treatment in an inert atmosphere to obtain the CoS2 / MoS2 / CoMoO4 / NF catalyst. The CoS2 / MoS2 self-supporting heterojunction catalyst provided by the invention is a bimetallic sulfide heterojunction catalyst, components of the CoS2 / MoS2 self-supporting heterojunction catalyst have a synergistic effect, the CoS2 / MoS2 self-supporting heterojunction catalyst can adjust the electronic state and improve the catalytic activity, and meanwhile, the CoS2 / MoS2 self-supporting heterojunction catalyst has richer catalytic active sites and excellent SOR catalytic activity. More importantly, the heterojunction of the CoS2 / MoS2 / CoMoO4 / NF catalyst disclosed by the invention is beneficial to adjusting spin polarization and improving the SOR catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of new energy material technology and electrochemical catalysis technology, and in particular to a spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst; it also relates to a preparation method of the catalyst and its application in the sulfide ion oxidation reaction in electrocatalytic seawater electrolysis to produce hydrogen. Background Art

[0002] Hydrogen has a high energy density (142MJ·kg -1 ), zero carbon emissions and renewability, it is considered to be a promising clean energy carrier. Seawater electrolysis (SWE) can achieve sustainable production of high-purity hydrogen and help protect scarce freshwater resources. However, the inherent slow kinetics of the anodic oxygen evolution reaction (OER) and the chlorine evolution reaction (CER) limit its development. In this context, small molecule electrocatalytic oxidation instead of slow water oxidation is a promising energy-saving and clean hydrogen production strategy, in which the more thermodynamically favorable sulfur ion oxidation reaction (SOR, S 2- =S+2e - , -0.48V vs.RHE) to replace the anode OER is conducive to reducing the electrolysis voltage to achieve energy-saving hydrogen production, and can also avoid CER. In addition, SOR can quickly degrade sulfur-containing wastewater (0.1 to 4wt.% S 2- ) and converts it into the value-added product S8 without the need for additional oxidants or laborious separation. The hybrid seawater electrolyzer (HSE) constructed by sulfide oxidation reaction (SOR) coupled with cathode hydrogen evolution reaction (HER) provides an innovative approach to achieve efficient and energy-saving hydrogen production and degradation of sulfur-containing wastewater with both economic and environmental benefits.

[0003] However, there are few studies on SOR-assisted water electrolysis for hydrogen production, and since SOR is a complex reaction process involving multiple electron transfers and the formation of multiple polysulfide intermediates, S 2-It is easy to corrode or poison the catalyst, resulting in poor activity and stability of the catalyst, which cannot meet the actual high-current industrial application. Therefore, the development of highly catalytically active, stable and low-cost SOR and HER bifunctional catalysts still faces great challenges. In the prior art, catalysts based on transition metal-based oxides, phosphides and sulfides have excellent catalytic activity and are widely concerned. Among them, transition metal sulfides are a very promising catalyst in the field of SOR due to their high conductivity and ability to promote the conversion of polysulfides. For example, the journal Green Chemistry (DOI: 10.1039 / d1gc01857d) reported that Cu2S microsheet catalysts (Cu2S / NF) supported on nickel foam (NF) substrates were used to catalyze SOR-assisted electrochemical water decomposition, which required a voltage of 0.26V (vs.RHE) to drive 10mA·cm -2 The current density is low, and its catalytic performance is poor. In the journal Chemical Engineering Journal (DOI: 10.1016 / j.cej.2021.134472), a leaf-shaped cobalt-doped nickel sulfide (Co-Ni3S2) was synthesized on a nickel mesh by first using an electrodeposition method, followed by a simple hydrothermal sulfidation. The Co-Ni3S2 electrocatalyst was used for SOR, which drove 100 mA cm -2 The current density requires a voltage of 0.59 V (vs. RHE) and can run stably for 24 h, but its catalytic activity and cycle stability are poor. In summary, the existing transition metal-based SOR catalysts have poor catalytic activity and stability, and the development of highly active and stable catalysts still faces great challenges. Summary of the invention

[0004] In view of the above-mentioned shortcomings, the present invention provides a spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst and its preparation method and application. The present invention successfully synthesized a spin-polarized CoS2 / MoS2 heterojunction catalyst on a single crystal CoMoO4 precursor by a hydrothermal method and a thermal sulfurization method. The study found that the bimetallic sulfide heterojunction catalyst has a synergistic effect between its components, which can adjust the electronic state and improve the catalytic activity. At the same time, it has more abundant catalytic active sites and has excellent SOR catalytic activity. More importantly, the present invention found that CoS2 / MoS2 heterogeneity is conducive to adjusting spin polarization and improving SOR catalytic activity.

[0005] In order to achieve the above object, the present invention provides a method for preparing a spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst, comprising the following steps:

[0006] S1. Preparation of CoMoO4 / NF precursor:

[0007] Co(NO3)2·6H2O and (NH4)6Mo7O 24 ·4H2O is hydrothermally treated on nickel foam NF to obtain single crystal CoMoO4 nanorods to obtain a precursor CoMoO4 / NF; wherein the nickel foam NF is pretreated nickel foam;

[0008] Preparation of S2, CoS2 / MoS2 / CoMoO4 / NF catalysts:

[0009] The precursor CoMoO4 / NF is cut and placed downstream of a tubular furnace, and subjected to thermal sulfurization treatment in an inert atmosphere to obtain a CoS2 / MoS2 / CoMoO4 / NF catalyst; wherein sublimated sulfur powder is placed upstream of the tubular furnace; and the CoS2 / MoS2 / CoMoO4 / NF catalyst is a spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst.

[0010] According to one aspect of the present invention, in step S1, the temperature of the hydrothermal treatment is 120-150° C., and the time is 4-8 hours.

[0011] According to one aspect of the present invention, in step S1, the Co(NO3)2·6H2O and (NH4)6Mo7O 24 ·4H2O molar ratio is 5:1-9:1.

[0012] According to one aspect of the present invention, in step S1, the pretreatment is specifically: ultrasonicating the nickel foam NF in hydrochloric acid, washing it with deionized water and ethanol for multiple times, and then drying it.

[0013] According to one aspect of the present invention, in step S2, the temperature of the thermal vulcanization treatment is 300-500° C. and the time is 2-5 hours.

[0014] According to one aspect of the present invention, in step S2, the heating rate of the tube furnace is 1-5°C·min -1 .

[0015] According to one aspect of the present invention, in step S2, the inert atmosphere is one or more of nitrogen or argon.

[0016] Based on the same inventive concept, the present invention also provides a spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst prepared by any of the above preparation methods.

[0017] Based on the same inventive concept, the present invention also provides an application of a spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst prepared by any of the above preparation methods in electrocatalytic seawater electrolysis to produce hydrogen.

[0018] Beneficial effects of the present invention:

[0019] (1) The present invention is the first to successfully synthesize a spin-polarized CoS2 / MoS2 heterojunction catalyst on a single-crystal CoMoO4 precursor by thermal sulfurization, and the first to apply this CoS2 / MoS2 heterojunction to the field of sulfide ion oxidation-assisted seawater electrolysis for hydrogen production;

[0020] (2) The CoS2 / MoS2 / CoMoO4 / NF catalyst prepared by the present invention is superior to the reported SOR catalysts (such as Fig. 9 As shown in Figure 2, the CoS2 / MoS2 / CoMoO4 / NF catalyst with spin polarization characteristics and interface synergistic effect is beneficial to improving the electron transfer rate and more abundant catalytic active sites, thereby improving the SOR catalytic activity;

[0021] (3) The spin polarization characteristics of the CoS2 / MoS2 / CoMoO4 / NF catalyst prepared by the present invention are beneficial to promoting the migration of electrons on the catalyst surface and can improve the adsorption capacity of polysulfide intermediates;

[0022] (4) The CoS2 / MoS2 / CoMoO4 / NF catalyst prepared by the present invention can also stably operate for more than 70 hours under high current, and has excellent stability. The present invention is suitable for large-scale industrial electrolysis of water to produce hydrogen;

[0023] (5) The SOR coupled HER hybrid seawater electrolyzer constructed by the present invention using CoS2 / MoS2 / CoMoO4 / NF catalyst ( Fig.13 ) can also achieve energy-saving hydrogen production. In addition, SOR can quickly degrade sulfur ions and convert them into high-value sulfur (S8)( Fig.15 ), achieving the purification of sulfur-rich wastewater without the need for additional oxidants or laborious separation. The invention has economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The present invention is a flow chart for preparing the spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst;

[0025] Figure 2 Physical pictures of the pretreated nickel foam NF, CoMoO4 / NF sample and CoS2 / MoS2 / CoMoO4 / NF catalyst prepared in Example 1 of the present invention;

[0026] Figure 3The SEM images of the products prepared in Example 1 and Comparative Example 2 of the present invention; wherein (a) is the precursor CoMoO4 / NF sample prepared in Comparative Example 2; (b) is the CoS2 / MoS2 / CoMoO4 / NF catalyst prepared in Example 1;

[0027] Figure 4 The HRTEM images of different selected areas of the product prepared in Example 1 of the present invention and the HRTEM images of the product prepared in Comparative Example 2; wherein (a) is the HRTEM image of the selected area 1 of the CoS2 / MoS2 / CoMoO4 / NF catalyst prepared in Example 1; (b) is the HRTEM image of the selected area 2 of the CoS2 / MoS2 / CoMoO4 / NF catalyst prepared in Example 1; (c) is the precursor CoMoO4 / NF sample prepared in Comparative Example 2;

[0028] Figure 5 The XRD patterns of the final products prepared in Example 1 and Comparative Examples 2-4 of the present invention; wherein (a) is the XRD pattern of the final products obtained in Example 1 and Comparative Example 2; (b) is the XRD pattern of the final products obtained in Comparative Examples 3-4;

[0029] Figure 6 The SOR linear scanning curve of the CoS2 / MoS2 / CoMoO4 / NF catalyst of Example 1 of the present invention in a 1.0MNaOH electrolyte containing different concentrations of Na2S;

[0030] Figure 7 The SOR linear scanning curves of the final products prepared in Example 1 and Comparative Examples 2-4 of the present invention in an electrolyte of 1.0M Na2S and 1.0M NaOH;

[0031] Figure 8 Comparison of SOR and OER linear scan curves of CoS2 / MoS2 / CoMoO4 / NF catalyst of Example 1 of the present invention;

[0032] Fig. 9 This is a comparison chart of the activity of the CoS2 / MoS2 / CoMoO4 / NF catalyst prepared in Example 1 of the present invention and the reported SOR;

[0033] Fig.10 The CoS2 / MoS2 / CoMoO4 / NF catalyst of Example 1 of the present invention was subjected to a current density of 100 mA·cm -2 SOR stability test curve in 1.0M NaOH+1.0M Na2S electrolyte under the conditions;

[0034] Fig.11The CoS2 / MoS2 / CoMoO4 / NF catalyst of Example 1 of the present invention was subjected to a current density of 300 mA·cm -2 SOR stability test curve in 1.0M NaOH+1.0M Na2S electrolyte under the conditions;

[0035] Fig.12 The linear scanning curves of the final products prepared in Example 1 and Comparative Examples 2-4 of the present invention in 1.0MNaOH+0.5MNaCl electrolyte;

[0036] Fig.13 This is a physical picture of a mixed seawater electrolyzer assembled using the CoS2 / MoS2 / CoMoO4 / NF catalyst prepared in Example 1 of the present invention;

[0037] Fig.14 Comparison of linear scan curves of a hybrid seawater electrolyzer (HSE) assembled with the CoS2 / MoS2 / CoMoO4 / NF catalyst prepared in Example 1 and an alkaline seawater electrolyzer (ASE) according to the present invention;

[0038] Fig.15 The XRD diagram and physical image of the sulfur product obtained by treating the electrolyte with concentrated sulfuric acid after the CoS2 / MoS2 / CoMoO4 / NF catalyst prepared in Example 1 of the present invention is as follows;

[0039] Fig.16 The corresponding density diagrams of MoS2, CoS2 and CoS2 / MoS2 of the present invention; wherein (a) is a catalyst containing CoS2; (b) is a catalyst containing MoS2; (c) is a catalyst containing CoS2 / MoS2;

[0040] Fig.17 It is the free energy required for each step of SOR catalyzed by MoS2, CoS2 and CoS2 / MoS2 of the present invention. DETAILED DESCRIPTION

[0041] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.

[0042] The present invention provides a method for preparing a spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst, comprising the following steps:

[0043] S1. Preparation of CoMoO4 / NF precursor:

[0044] Co(NO3)2·6H2O and (NH4)6Mo7O 24 ·4H2O is hydrothermally treated on nickel foam NF to obtain single crystal CoMoO4 nanorods to obtain a precursor CoMoO4 / NF; wherein the nickel foam NF is pretreated nickel foam;

[0045] Preparation of S2, CoS2 / MoS2 / CoMoO4 / NF catalysts:

[0046] The precursor CoMoO4 / NF is cut and placed downstream of a tubular furnace, and subjected to thermal sulfurization treatment in an inert atmosphere to obtain a CoS2 / MoS2 / CoMoO4 / NF catalyst; wherein sublimated sulfur powder is placed upstream of the tubular furnace; and the CoS2 / MoS2 / CoMoO4 / NF catalyst is a spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst.

[0047] In one embodiment of the present invention, in step S1, the temperature of the hydrothermal treatment is 120-150° C., and the time is 4-8 hours.

[0048] In one embodiment of the present invention, in step S1, the Co(NO3)2·6H2O and (NH4)6Mo7O 24 ·4H2O molar ratio is 5:1-9:1.

[0049] In one embodiment of the present invention, in step S1, the amount of Co(NO3)2·6H2O is 1.2-1.8 mmol, (NH4)6Mo7O 24 The amount of 4H2O used is 0.1-0.5mmol.

[0050] In one embodiment of the present invention, in step S1, the pretreatment is specifically: ultrasonicating the nickel foam NF in hydrochloric acid, washing it with deionized water and ethanol for multiple times, and then drying it.

[0051] In one embodiment of the present invention, in step S2, the temperature of the thermal vulcanization treatment is 300-500° C. and the time is 2-5 hours.

[0052] In one embodiment of the present invention, in step S2, the heating rate of the tube furnace is 1-5°C·min -1 .

[0053] In one embodiment of the present invention, in step S2, the inert atmosphere is one or more of nitrogen or argon.

[0054] The following is further described in conjunction with specific embodiments and comparative examples.

[0055] Example 1

[0056] Preparation of CoS2 / MoS2 / CoMoO4 / NF catalyst, the preparation flow chart is as follows Figure 1 As shown:

[0057] Pretreatment of nickel foam:

[0058] The nickel foam was ultrasonically treated in 3 mol / L hydrochloric acid for 10 minutes to remove surface impurities, then washed with deionized water and ethanol for more than three times, and dried in an oven at 60° C. to obtain a pretreated nickel foam NF.

[0059] Preparation of CoMoO4 / NF precursor:

[0060] Weigh 1.5mmolCo(NO3)2·6H2O and 0.3mmol(NH4)6Mo7O 24 ·4H2O was added to 30mL of deionized water, and the pretreated nickel foam NF was placed in the vigorously stirred and fully dissolved solution, and then the solution was transferred to a 50mL polytetrafluoroethylene autoclave liner and kept at 150°C for 6 hours. After the reaction was completed, the obtained CoMoO4 / NF was rinsed with deionized water and dried at 60°C for 12h to obtain a purple precursor CoMoO4 / NF sample.

[0061] Preparation of CoS2 / MoS2 / CoMoO4 / NF catalyst:

[0062] The precursor CoMoO4 / NF obtained by the reaction was cut into 1×1 cm 2 The small pieces were placed in a porcelain boat, and then the above samples were placed downstream of the tube furnace, and 0.5g of sublimated sulfur powder was placed upstream. The tube furnace was heated at 2℃·min -1 The tube furnace was heated to 300 °C at a heating rate of 100 °C and maintained in a N2 atmosphere for 2 h. After the tube furnace was cooled to room temperature, the black CoS2 / MoS2 / CoMoO4 / NF catalyst was taken out.

[0063] The pretreated nickel foam NF, CoMoO4 / NF sample and CoS2 / MoS2 / CoMoO4 / NF catalyst prepared in the above steps are as follows: Figure 2 shown.

[0064] Comparative Example 1

[0065] Preparation of pretreated nickel foam NF

[0066] The nickel foam was ultrasonically treated in 3 mol / L hydrochloric acid for 10 minutes to remove surface impurities, then washed with deionized water and ethanol for more than three times, and dried in an oven at 60° C. to obtain a pretreated nickel foam NF.

[0067] Comparative Example 2

[0068] Preparation of CoMoO4 / NF precursor

[0069] Pretreatment of nickel foam:

[0070] The nickel foam was ultrasonically treated in 3 mol / L hydrochloric acid for 10 minutes to remove surface impurities, then washed with deionized water and ethanol for more than three times, and dried in an oven at 60° C. to obtain a pretreated nickel foam NF.

[0071] Preparation of CoMoO4 / NF precursor:

[0072] Weigh 1.5mmolCo(NO3)2·6H2O and 0.3mmol(NH4)6Mo7O 24 ·4H2O was added to 30mL of deionized water, and the pretreated nickel foam NF was placed in the vigorously stirred and fully dissolved solution, and then the solution was transferred to a 50mL polytetrafluoroethylene autoclave liner and kept at 150°C for 6 hours. After the reaction was completed, the obtained CoMoO4 / NF was rinsed with deionized water and dried at 60°C for 12h to obtain a purple precursor CoMoO4 / NF sample.

[0073] Comparative Example 3

[0074] Preparation of CoS2 / NF catalyst

[0075] Pretreatment of nickel foam:

[0076] The nickel foam was ultrasonically treated in 3 mol / L hydrochloric acid for 10 minutes to remove surface impurities, then washed with deionized water and ethanol for more than three times, and dried in an oven at 60° C. to obtain a pretreated nickel foam NF.

[0077] Preparation of CoS2 / NF catalyst:

[0078] Dissolve 6mmol Co(NO3)2·6H2O, 4mmol NH4F and 20mmol urea in 40mL deionized water, transfer the solution to 50mL of polytetrafluoroethylene autoclave liner, put the pretreated nickel foam NF into the solution, and keep it at 110℃ for 8 hours. After the reaction is completed, take out the pink precursor Co(OH)2 / NF, wash it with deionized water several times, and dry it in a 60℃ oven overnight.

[0079] The Co(OH)2 / NF precursor obtained by the reaction was cut into 1×1 cm 2 The small pieces were placed in a porcelain boat, and then the sample was placed downstream of the tube furnace, and 1.0 g of sublimated sulfur powder was placed upstream. The tube furnace was heated at 5 °C·min -1 The tube furnace was heated to 400 °C at a heating rate of 100 °C and maintained in a N2 atmosphere for 2 h. After the tube furnace was cooled to room temperature, the black CoS2 / NF catalyst was taken out.

[0080] Comparative Example 4

[0081] Preparation of MoS2 / NF catalyst

[0082] Pretreatment of nickel foam:

[0083] The nickel foam was ultrasonically treated in 3 mol / L hydrochloric acid for 10 minutes to remove surface impurities, then washed with deionized water and ethanol for more than three times, and dried in an oven at 60° C. to obtain a pretreated nickel foam NF.

[0084] Preparation of MoS2 / NF catalyst:

[0085] Weigh 0.6g Na2MoO4·2H2O and 0.7g thioacetamide and add them to 40mL deionized water and stir to dissolve for 2 hours. Transfer the solution to a 50mL polytetrafluoroethylene autoclave liner, put the pretreated NF into the solution, and keep it at 180℃ for 18 hours. After the reaction is completed, take it out, wash it with deionized water several times, and dry it in a 60℃ oven overnight to obtain a black MoS2 / NF catalyst.

[0086] Performance testing and result analysis:

[0087] Morphological characterization:

[0088] The final materials obtained in Example 1 and Comparative Example 2 were subjected to scanning electron microscope microstructure analysis. Figure 3 ,like Figure 3 As shown, the CoMoO4 nanorod arrays are evenly distributed on the entire nickel foam substrate. After thermal sulfurization, the nanorod morphology of the CoS2 / MoS2 / CoMoO4 / NF catalyst is well maintained, but the nanorods are slightly cracked and their surface becomes rougher.

[0089] The final materials obtained in Example 1 and Comparative Example 2 were subjected to high-resolution transmission electron microscope microstructure analysis. Figure 4 ,Depend on Figure 4As shown in (c), the present application prepares single-crystal CoMoO4 nanorods on nickel foam NF through hydrothermal treatment, and its obvious single-crystal properties can provide a fast transmission path for ions or electrons; as shown in Figure (a), the lattice fringes with a plane spacing of 0.360nm are related to the (002) crystal plane of CoMoO4, the lattice fringes of 0.264nm and 0.252nm are related to the (101) and (102) crystal planes of MoS2, respectively, and the lattice fringes of 0.325nm correspond to the (111) crystal plane of CoS2; Figure 4 (b) shows that the lattice fringes with a crystal spacing of 0.266nm are related to the (101) crystal plane of MoS2, while the lattice fringes with crystal spacings of 0.272nm and 0.275nm are related to the (200) crystal plane of CoS2. It is worth noting that the HRTEM image shows that there are obvious interfaces between CoS2, MoS2 and CoMoO4. This shows that we have successfully prepared the heterojunction CoS2 / MoS2 / CoMoO4 / NF catalyst on the precursor CoMoO4 / NF.

[0090] The final materials obtained in Example 1 and Comparative Examples 2-4 were subjected to XRD analysis. Figure 5 As shown in the figure, the CoMoO4 precursor is mainly composed of three strong diffraction peaks of CoMoO4 (PDF#25-1434) and NF (PDF#87-0712). After thermal sulfurization, the diffraction peaks in the XRD spectrum of the catalyst correspond to CoS2 (PDF#41-1471), MoS2 (PDF#37-1492) and CoMoO4 (PDF#25-1434), which indicates that the precursor CoMoO4 / NF was successfully prepared after thermal sulfurization to form a heterojunction CoS2 / MoS2 / CoMoO4 / NF catalyst. In addition, Figure 5 It can be seen that Comparative Examples 3 and 4 successfully prepared CoS2 (PDF#41-1471) catalyst and MoS2 (PDF#37-1492) catalyst.

[0091] Electrochemical performance test:

[0092] The material finally obtained in Example 1 was charged into 1.0M NaOH+0.1M Na2S, 1.0M NaOH+0.5M Na2S and 1.0M NaOH+1.0M Na2S solutions by three electrodes at 2mV·s -1 SOR linear sweep voltammetry (LSV) test was performed at a scan rate of Figure 6 The results show that the CoS2 / MoS2 / CoMoO4 / NF catalyst finally obtained in Example 1 exhibits excellent SOR activity in 1.0M NaOH electrolyte containing different concentrations of Na2S, and the S 2-With the increase of ion concentration, SOR activity was significantly enhanced.

[0093] The materials finally obtained from Example 1 and Comparative Examples 2-4 were subjected to a three-electrode reaction at 2 mV·s in 1.0 M NaOH + 1.0 M Na2S. -1 SOR linear sweep voltammetry (LSV) test was performed at a scan rate of Figure 7 , Table 1; CoS2 / MoS2 / CoMoO4 / NF catalyst exhibits excellent SOR activity in 1.0MNaOH+1.0M Na2S electrolyte, requiring only extremely low potentials of 0.258 and 0.326 V vs. RHE to drive current densities of 100 and 300 mA cm -2 , its SOR catalytic activity is significantly better than that of Comparative Examples 2-4 (CoS2 / NF, MoS2 / NF and CoMoO4 / NF). Figure 7 The catalyst in Example 1 was reacted in 1.0M NaOH+1.0M Na2S with three electrodes at 2mV·s -1 The SOR linear sweep voltammetry (LSV) test was performed at a scan rate of 2.5 % and compared with the OER linear sweep voltammetry (LSV) test under the same conditions. The results are shown in Figure 2. Figure 8 As shown by Figure 8 It can be seen that the linear scanning curves of CoS2 / MoS2 / CoMoO4 / NF catalyst in 1.0M NaOH electrolyte with or without Na2S can reach 100 and 300 mA cm -2 At the current density of 2.5 M Na2S, the voltage required for OER is 1.55 and 1.67 V vs. RHE. However, when 1.0 M Na2S is added to the alkaline electrolyte, the anode SOR potential required to achieve the same current density is greatly reduced to 0.258 and 0.326 V, which indicates that SOR replacing OER is beneficial to achieve energy-saving hydrogen production.

[0094] Table 1 Different catalysts driving 100 mA cm -2 and 300mA·cm -2 The voltage required for each current density

[0095]

[0096] The CoS2 / MoS2 / CoMoO4 / NF catalyst obtained in Example 1 was subjected to chronoamperometry (CP) in a three-electrode system in a 1.0 M NaOH + 1.0 M Na2S solution at 100 mA cm -2 and 300mA·cm -2 Stability test was carried out at a current density of Figure 10-11The results show that the CoS2 / MoS2 / CoMoO4 / NF catalyst of Example 1 has excellent stability and high current density of 300 mA cm -2 It can also run stably for more than 70 hours under low temperature, which can meet the requirements of large current applications in actual industrialization.

[0097] The materials finally obtained from Example 1 and Comparative Examples 2-4 were subjected to a three-electrode reaction at 2 mV·s in 1.0 M NaOH + 0.5 M NaCl. -1 HER linear sweep voltammetry (LSV) test was performed at a scan rate of Fig.12 The CoS2 / MoS2 / CoMoO4 / NF catalyst only needs 0.204 and 0.286 V vs. RHE to drive current densities of 100 and 300 mA cm in 1.0 M NaOH + 0.5 M NaCl electrolyte. -2 , and its HER catalytic activity is significantly better than that of CoS2 / NF and CoMoO4 / NF.

[0098] Based on the high HER and SOR activity of the CoS2 / MoS2 / CoMoO4 / NF catalyst prepared in Example 1, it was used for cathode seawater hydrogen evolution (1.0 M NaOH + 0.5 M NaCl) and anode sulfur ion oxidation (1.0 M NaOH + 1.0 M Na2S). Fig.13 The hybrid seawater electrolyzer (HSE) shown in FIG. 1 can realize energy-saving hydrogen production from seawater and sulfur-containing wastewater treatment. Fig.13 As shown, the cation exchange membrane (Nafion 117) is Na + Provide channels to separate the cathode and anode regions. Fig.14 As shown in Figure 2, HSE can reach 100 mA cm with a low voltage of only 0.772 V. -2 , compared with the voltage of 1.733V required by the alkaline seawater tank, HSE reduces the energy consumption by ~56%, and SOR-assisted seawater electrolysis can achieve the effect of energy-saving hydrogen production.

[0099] The electrolyte of the catalyst prepared in Example 1 after 80h CP test in SOR was treated with concentrated sulfuric acid: in an ice bath, concentrated H2SO4 solution was dripped into the electrolyte after SOR until the pH was 1. Sulfur was precipitated as a yellow product, and a light yellow powder product ( Fig.15 In addition, Fig.15 The XRD spectrum of the sample confirmed that the powder product collected after acid treatment corresponds to elemental sulfur (S8, PDF#78-1889).

[0100] DFT theoretical calculations were used to study the SOR activity on different polysulfide intermediates, namely MoS2, CoS2 and CoS2 / MoS2. Fig.16 This indicates that compared to MoS2, spin-polarized CoS2 and CoS2 / MoS2 require lower energy barriers at each step of the SOR reaction. More importantly, CoS2 / MoS2 has a lower energy barrier to overcome, indicating that the CoS2 / MoS2 heterojunction catalyst is more conducive to the adsorption of sulfur and the catalysis of polysulfides and has excellent SOR catalytic performance. Fig.16 (a)-(c) show that there are significant differences in the local DOS around the Fermi level (EF). The wide bandgap of MoS2 at the Fermi level limits its electron transfer. However, CoS2 and CoS2 / MoS2 have no bandgap at the Fermi level and exhibit high conductivity. In addition, Fig.16 (a) and 16(c) show the significant difference in the electron state density of spin-up and spin-down near the Fermi level EF, indicating that CoS2 and CoS2 / MoS2 are spin-polarized magnetic materials. This spin polarization property is beneficial to promote the migration of electrons on the catalyst surface and improve the adsorption capacity of polysulfide intermediates.

[0101] Experiments and DFT calculations reveal that the heterojunction modulates the spin polarization of CoS2 / MoS2, optimizes the free energy and adsorption energy of the reaction intermediates, and thus enhances the SOR activity. Fig.16 and Fig.12 As shown in Figure 2, compared with CoS2 and MoS2, the spin-polarized heterojunction catalyst containing CoS2 / MoS2 has better SOR and HER activities. Fig.11 As shown, CoS2 / MoS2 / CoMoO4 / NF can also operate stably for more than 70 hours under high current, and has excellent stability. The present invention is suitable for large-scale industrial electrolysis of water to produce hydrogen.

[0102] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst, characterized in that: The following steps are involved: S1. Preparation of CoMoO4 / NF precursor: Co(NO3)2·6H2O and (NH4)6Mo7O 24 ·4H2O is hydrothermally treated on nickel foam NF to obtain single crystal CoMoO4 nanorods to obtain a precursor CoMoO4 / NF; wherein the nickel foam NF is pretreated nickel foam; Preparation of S2, CoS2 / MoS2 / CoMoO4 / NF catalysts: The precursor CoMoO4 / NF is cut and placed downstream of a tubular furnace, and subjected to thermal sulfurization treatment in an inert atmosphere to obtain a CoS2 / MoS2 / CoMoO4 / NF catalyst; wherein sublimated sulfur powder is placed upstream of the tubular furnace; and the CoS2 / MoS2 / CoMoO4 / NF catalyst is a spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst.

2. The method for preparing the spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst according to claim 1, characterized in that: In step S1, the temperature of the hydrothermal treatment is 120-150° C. and the time is 4-8 hours.

3. The method for preparing the spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst according to claim 2, characterized in that: In step S1, the Co(NO3)2·6H2O and (NH4)6Mo7O 24 ·4H2O molar ratio is 5:1-9:

1.

4. The method for preparing the spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst according to claim 1, characterized in that: In step S1, the pretreatment is specifically: ultrasonicating the nickel foam NF in hydrochloric acid, washing it with deionized water and ethanol for multiple times, and then drying it.

5. The method for preparing the spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst according to claim 1, characterized in that: In step S2, the temperature of the thermal vulcanization treatment is 300-500°C and the time is 2-5 hours.

6. The method for preparing the spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst according to claim 1, characterized in that: In step S2, the heating rate of the tube furnace is 1-5°C·min -1 .

7. The method for preparing the spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst according to claim 1, characterized in that: In step S2, the inert atmosphere is one or more of nitrogen or argon.

8. A spin-polarized CoS2 / MoS2 self-supporting heterojunction catalyst prepared by the preparation method as described in any one of claims 1-7.

9. Use of a CoS2 / MoS2 self-supporting heterojunction catalyst prepared by the preparation method according to any one of claims 1 to 7 or the CoS2 / MoS2 self-supporting heterojunction catalyst according to claim 8 in electrocatalytic seawater electrolysis to produce hydrogen.

Citation Information

Patent Citations

  • Carbon cloth loaded CoS2 / MoS2 heterojunction composite material and preparation method and application thereof

    CN111495394A

  • Preparation method of CoS / MoS2 heterojunction catalytic material with double built-in electric fields

    CN117535724A

  • Preparation method and application of cobalt-molybdenum heterojunction catalyst rich in sulfur vacancies

    CN117587455A